Secret People - Anderson, John; Harrison, Laura (United States, 1998)
Soros Documentary Fund From the 1920's to the late 1950's United States citizens with leprosy were forcibly transported, often in chains and in sealed box cars, to Carville, America's last leprosarium. Abandoned by family and friends, stripped of their constitutional rights to vote, to get married and bear children, even to use the telephone, many of Carville's "residents" nonetheless accomplished the remarkable act of transforming their prison into a home. “Secret People” tells a damning story of outrageous discrimination and stigma in the American public health system, interwoven with a haunting and bittersweet chronicle of human courage and perseverance.